Implementation of an IoT-Based Smart Water System as a Means in Monitoring the Use of Consumer Water Debit Using Photovoltaic in Seboro Village Probolinggo - Moh Zainul Falah; Abdullah Iskandar Syah; Wahyu Tri Handoko; Nanik Nor Laila; Faizah Nur Faridah; Muladi Muladi (Bulletin of Community Engagement, 2023)
Seboro Village, which is located in Probolinggo Regency, has a BUMDES whose business unit is the “Sumber Abadi” Drinking Water Supply Facility Management Group (KP.SPAM). The group is engaged in the field of consumption water which will be used by the people of Seboro Village who subscribe. In its implementation, the manager will monitor the use of conventional consumer water discharge by coming to each house that subscribes as a step to calculate the cost of billing water usage per month. This community service activity program aims to make it easier for water managers to monitor the use of consumer water discharge in the "Sumber Abadi" Drinking Water Procurement Facility Management Group (KP.SPAM) by creating an IoT-based smart water system using Photovoltaic. With the smart water system, it is hoped that the manager's work in monitoring the use of water discharge for consumers will be more effective and efficient because the manager does not need to record directly to the location of the consumer's home and can do this by monitoring the use of water discharge using apps/websites remotely. Another advantage of this tool is that data storage management for water discharge usage is more regular because the data will be stored on a cloud server. The source of electricity from an IoT-based smart water system device using photovoltaic as a renewable energy from solar irradiation is converted to electrical energy as a step from environmentally friendly energy. Keywords: Smart Water System, IoT, Photovoltaic, Consumer Water Debit